Production and social use of scientific knowledge on health: Approaching the work of social researchers - Echeverry-Mejía, Jorge-Andrés (2021)
The aim of this work was to analyze the dynamics of production and social use of scientific knowledge in health from a socio-cognitive approach to the trajectories of researchers from two Latin American public universities: the University of Antioquia (Colombia) and the National University of Córdoba (Argentina). The analysis period ran from 2016 to 2018. A qualitative approach was adopted, employing observation, documentary review and semistructured interviews as tools for information gathering. Contributions from areas of study including science, technology and society were adopted as part of the conceptual basis. Four aspects of inquiry were employed: the socio-institutional dimension, scientific and technological research regimes, the cognitive dimension, and the social utility of scientific knowledge. The findings demonstrate a significant heterogeneity in approaches to the phenomena associated with health, indicating certain points of contact with regard to collective health as a Latin American tradition.